Pengaruh Multiple Large Shareholder Terhadap Nilai Perusahaan - Annisa Hastriyana; Salma Taqwa (Universitas Negeri Padang, 2019)
This study aims to examine the effect of multiple large shareholder on the firms value. This study is classified as causative research. The population in this study are property and real estate companies listed on the Indonesian Stock Exchange period of 2015 to 2017. By using purposive sampling method, there were 37 companies as the research’s sample. Multiple large shareholder variable are measured by the number and percentage of multiple large shareholder. The type of data used is secondary data obtained from www.idx.co.id and used is panel regression analysis. The results of this study indicate that precentage of multiple large shareholder has a negative and significant effect on firms value, andnumber of multiple large shareholder there is not effect on frims value.